If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = -2(4d + 5) Reorder the terms: 0 = -2(5 + 4d) 0 = (5 * -2 + 4d * -2) 0 = (-10 + -8d) Solving 0 = -10 + -8d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '8d' to each side of the equation. 0 + 8d = -10 + -8d + 8d Remove the zero: 8d = -10 + -8d + 8d Combine like terms: -8d + 8d = 0 8d = -10 + 0 8d = -10 Divide each side by '8'. d = -1.25 Simplifying d = -1.25
| h(t)=10-3t | | -3(n+2)=-6(n-1) | | 9x-4=2+3 | | 90+(-105)= | | Cx+3n=5a | | 3m-4=-4-6m-m | | -12+(-15)= | | 5=4k+2-1 | | -20*(-5)= | | 10x+15=125 | | 3x-4(x+5)=17 | | 6x+2=5(x-4)+6 | | a+r=z | | -3(6p+5)-2(3-14p)=3(9+3p) | | w-2=-43 | | (x+2)+(4x-147)=180 | | 125x+15=10 | | 7x-(2x+9)=7 | | 4(-4x+5)=-8 | | 16=2v+6 | | h(x)=x^2-2x+3 | | 70=-5m+10 | | (13b-7)-4(3b+3)=-7 | | 8.2+(-3.5)= | | 3/6=x/10 | | -4(6+r)=-63 | | (x^4-y^4)(x^4+y^4)= | | 15=14-16.6m | | 10-9n-8n=-6(-6-9n)-4(11n-7) | | 38-5b=-3(-5-5b)+3b | | Y=x^12 | | 10/80=11/x |